Transient contact resistance in electrical connections with flat pins - Efimenko, A. A.; Merlyan, S. V. (Technology and design in electronic equipment, 2013)
On the basis of experimental research, the authors have obtained dependences allowing to find promptly and with a small amount of calculations the optimum pressure value for elastic elements of flat contacts with different coatings (tin-bismuth, nickel, palladium, silver, gold), using the preset value of contact resistance Rпер. Moreover, the obtained results of estimation of quantity and stability of Rпер allow choosing the optimal coating according to the operating conditions of the contacts.